Mechanical Behaviour of Two Beniseed Accessions under Compression Loading - Olayanju, TMA; Ogunjinrin, O (Journal of Agricultural Engineering, 2003)
Some mechanical properties of two beniseed accessions (Yandev-55 and E8) of relevance to oil expression were determined at moisture content levels of 4.1, 5.3 and 7.7 per cent (wet basis). The properties were the force required, the deformation sustained and the energy needed to rupture and express oil from the seed. A2 x 5 factorial experiment in completely randomized design with a total of 120 observations was used for each of the parameters.The applied force, sustained deformation and energy required to rupture and express oil from the seed ranged from 7.73 to 29.40N, 0.17 to 0.54mm and 0.4 to 1.1 MJ for whole and dehulled seeds, respectively, at 4.1% moisture content. These values increased with the increase in moisture content. The mean values of all the parameters were higher when the seed. was dehulled than when left undehulled. The result of the statistical analysis shows that seed accession, preconditioning method and moisture content have significant effect on the studied parameters.